Surveillance on susceptibility of strains isolated from pediatric infections. Issue 3 (March 2019) - Sakata, Hiroshi; Watanabe, Akira; Iwata, Satoshi; Sato, Yoshitake; Suzuki, Kenji; Miyashita, Naoyuki; Hori, Seiji; Yamaguchi, Yoshio; Odajima, Masaaki; Katakuse, Yoshitaka; Hasegawa, Toshikazu; Maki, Nobuko; et al.
Abstract: During the period from January to December 2015, 104 Streptococcus pneumoniae strains, 129 Haemophilus influenzae strains and 54 Moraxella catarrhalis strains isolated from clinical specimens of pediatric infections in the national 16 institutions, studied susceptibilities of total 28 antibiotics, the capsular serotype for S. pneumoniae, the capsular b type and β-lactamase production capability for H. influenzae, and the β-lactamase production capability for M. catarrhalis were measured. In S. pneumoniae, the results showed that 68 strains (65.4%) were PSSP, 32 (30.8%) were PISP, and 4 (3.8%) were PRSP. The susceptibilities of TBPM and GRNX among oral antibiotics, and PAPM among injectable antibiotics demonstrated the lowest value with MIC90 ≤ 0.06 μg/mL. The most frequent distribution of S. pneumoniae serotypes was seen in 15B, followed by 19A, and 35B. Serotype strains contained in 13-valent pneumococcal conjugate vaccine (PCV13) were 19 strains (18.3%). In H. influenzae, the results showed that BLNAS accounted for 40 strains (31.0%), BLNAI for 28 strains (21.7%), BLNAR for 47 strains (36.4%), β-lactamase producing for 14 strains (10.8%). The susceptibilities of quinolones demonstrated the lowest outcome among oral antibiotics with MIC90 ≤ 0.06 μg/mL, and CTRX and TAZ/PIPC (TAZ4 fixed) among injectable antibiotics with MIC of 0.25 μg/mL. There was no detection of capsular type b strains. In M. catarrhalis, all the isolates were β-lactamase producing strains. The susceptibilities of TBPM, CPFX, TFLX and GRNX among oral antibiotics, and TAZ/PIPC (TAZ4 fixed), PAPM, MEPM and DRPM among injectable antibiotics demonstrated the lowest outcome with MIC of ≤0.06 μg/mL.